Soil physical properties and soybean productivity in succession to cover crops - Anschau Deimling, Katiely Aline; Pereira Seidel, Edleusa; Rosset, Jean Sérgio; Mottin, Marcos Cesar; da Rocha Herrmann, Daniela; Cecato Favorito, Amanda (Revista Ceres, 2025)
The objective of this research was to assess soybean productivity in succession to cover crops grown during the winter, in addition to assessing physical properties macroporosity (Ma), microporosity (Mi), total porosity (Pt), soil density (Sd) and aggregate stability by means of the following variables: aggregate stability index, geometric mean diameter and weighted mean diameter after soybean crop cultivation. The experiment was conducted in the municipality of Quatro Pontes, PR, using a randomized-block design with six treatments and four replications. Treatments consisted of soybean crop grown on top of different cover plants’ haystack: black oat, black oat + forage turnip, forage turnip, black oat + forage pea, forage pea and control. Significant differences were observed for soil macroporosity and density. At the depth of 0.10 m, the highest Ma was observed in the area with oat and oat + turnip haystack. At other depths, all cover crops were superior to control. Treatments with cover crops were efficient in reducing soil PR. As for soil aggregation, the treatment with pea was superior to control for weighted mean diameter. The treatments with soybean sown after intercropping obtained greater mass, as well as higher productivity.